Motor variability and skills monitoring in sports - Preatoni, E. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The aim of this paper is to present a brief review of the role that movement variability plays in the analysis of sports movement and in the monitoring of the athlete`s skills. Motor variability has been traditionally considered an unwanted noise to be reduced, but recent studies have revalued its role and have tried to understand whether it may contain information about the neuro-musculo-skeletal organisation. Issues concerning both views, different approaches to variability, open questions and future perspectives will be discussed.